Pembangunan Berkelanjutan di Asia Tenggara: Integrasi Praktik Ekonomi Hijau dalam Kebijakan Nasional - Yuningrat, Nova (Fakultas Ekonomi Universitas Gresik, 2025)
Sustainable development is a global priority, particularly in Southeast Asia, which faces significant challenges related to environmental degradation and climate change. Countries in the region, which rely heavily on natural resource-based sectors, need to integrate green economy principles into national development policies to mitigate environmental impacts and promote sustainable growth. This study aims to analyze the practice of green economy integration in national development policies in Southeast Asian countries and disseminate how these policies support the achievement of sustainable development. This study uses a quantitative approach with a descriptive and explanatory design, and data collection through surveys involving policymakers, the private sector, and international organizations in Indonesia, Malaysia, Thailand, Vietnam, and the Philippines. The results show that although green economy policies have been implemented in several countries, the main challenges faced are self-reliance in high-carbon-based sectors, a lack of supporting infrastructure, and limited funding. Therefore, governments need to improve policy coordination and provide greater incentives to the private sector to invest in green technologies.